The Rise and Fall of Bilharzia in Puerto Rico: Its Centennial 1904-2004 - Hillyer, George V. (Puerto Rico Health Sciences Journal, 2005)
Bilharzia (=schistosomiasis=esquistosomiasis=bilharziasis) is a chronic disease of humans in Africa, the Caribbean, South America and Asia caused by a parasite of the genus Schistosoma. Isaac Gonzalez Martinez established definitively the existence of human schistosomiasis in Puerto Rico in 1904 when he reported the discovery of fluke eggs in feces from two teenagers who had lived all their lives in the environs of Mayaguez, P.R. in the western part of the island. Today, in the absence of significant, active transmission and little or no evident morbidity, chemotherapy of serologically positive cases with follow-up to monitor decrease of antibody levels postchemotherapy is probably the most cost-effective means. The Vieques model has shown that human transmission can be stopped even in the presence of snails. Hopefully, soon we will have a bilharzia-free Puerto Rico, for a variety of reasons, but nevertheless bilharzia-free. There will come a day when we can say with confidence: “No hay bilharzia aqui.”